Non-inductive plasma start-up experiments on the TST-2 spherical tokamak using waves in the lower-hybrid frequency range. (5th June 2015) - Shinya, T.; Takase, Y.; Wakatsuki, T.; Ejiri, A.; Furui, H.; Hiratsuka, J.; Imamura, K.; Inada, T.; Kakuda, H.; Kasahara, H.; Kumazawa, R.; Moeller, C.; et al.
Abstract: Non-inductive plasma current start-up and sustainment by waves in the lower-hybrid frequency range (200 MHz) have been studied on the TST-2 spherical tokamak ( R 0 ⩽ 0.38 m, a ⩽ 0.25 m, B t0 ⩽ 0.3 T, I p ⩽ 0.14 MA) using three types of antenna: the 11-element inductively-coupled combline antenna, the dielectric loaded 4-waveguide array antenna, and the 13-element capacitively-coupled combline (CCC) antenna. The maximum plasma currents of 15 kA, 10 kA and 16 kA were achieved, respectively. The highest current drive figure of merit was achieved by the CCC antenna. The efficiency of current drive should improve by reducing prompt orbit losses of high energy electrons by operating at higher plasma current (to improve orbit confinement) and higher toroidal magnetic field (to improve wave accessibility to the plasma core), while keeping the density high enough (to avoid excessive acceleration of electrons), but under the 'density limit'.